H∞ synchronization of uncertain stochastic time-varying delay systems with exogenous disturbance via intermittent control. (October 2019) - Ding, Kui; Zhu, Quanxin
Highlights: This paper adopts the aperiodically intermittent control strategy, and its control period and control width are all variable, which is more suitable for the actual controller situation. In the structure of H ∞ control, the quantitative analysis method is adopted for the synchronization error of external disturbance, parameter uncertainty, and stochastic noise perturbation. In the analysis of stochastic synchronization, the paper is based on the PTDLF method, which can well grasp the performance of the closed-loop systems, and thus reduce the conservativeness. The almost sure exponential synchronization obtained in this work is a combination of the intermittent control strategy and the strong law of large numbers of local martingale. As far as we know, there is no such result in the current literature. Abstract: In this work, the drive-response H ∞ synchronization of stochastic time-varying systems with exogenous disturbance and parameter uncertainly via intermittent control is discussed. Based on a novel piecewise time dependent Lyapunov functional (PTDLF) and the strong low of large numbers for local martingales, the sufficient causes presented by linear matrix inequalities are established to ensure the mean square exponential synchronization and almost sure exponential synchronization with L 2 -gain performance for the stochastic drive-response system, respectively. In addition, two types of delay independent intermittent controllers are designed in view of the obtained synchronization standard. Finally, two numerical examples are given to illustrate the rationality and effectiveness of the method under investigation.